2019
DOI: 10.1111/aor.13476
|View full text |Cite
|
Sign up to set email alerts
|

Development of rear‐impeller axial flow blood pump for realization of axial flow blood pump installed at aortic valve position

Abstract: In this study, rear‐impeller axial flow blood pumps (RIAFBP) were developed to realize a trans‐valve axial ventricular assist device (VAD) which consists of the latter blood pump and a polymer monomembrane aortic valve, such as the jellyfish valve. The motor of the RIAFBP is installed in the left ventricle, and its impeller is placed at the aortic valve position. In the prototype RIAFBP, the rotation of the motor is sustained by polyethylene bushings. The RIAFBP has a length of 50 mm and diameter of 19.6 mm. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…In 1989, we propounded a concept of the valvo-pump that was an AFBP implanted at the aortic valve position, 12 and we and other groups have tried to develop AFBPs installed at the aortic valve position. 17,18 However, development of a miniature and high-power motor is a barrier to accomplishing this concept of the valvo-pump. In terms of current motor technology, partial left ventricular support is realistic for the concept of the valvo-pump.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 1989, we propounded a concept of the valvo-pump that was an AFBP implanted at the aortic valve position, 12 and we and other groups have tried to develop AFBPs installed at the aortic valve position. 17,18 However, development of a miniature and high-power motor is a barrier to accomplishing this concept of the valvo-pump. In terms of current motor technology, partial left ventricular support is realistic for the concept of the valvo-pump.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 Some research groups have also developed AFBPs implanted at the aortic valve position. [14][15][16] We have developed various AFBPs to accomplish the concept of the valvo-pump, and we are now developing a trans-valve LVAD that unites a rear-impeller AFBP 17 and a polymer membrane valve similar to the jelly-fish valve 18 ( Figure 1). The trans-valve LVAD can be stitched to the base of the aorta like an artificial aortic valve replacement.…”
Section: Introductionmentioning
confidence: 99%
“…Eiji Okamoto et al of Tokai University, Sapporo, Japan investigated rear‐impeller axial flow blood pumps (RIAFBP) to realize a trans‐valve axial VAD which consists of the latter blood pump and a polymer monomembrane aortic valve, such as the jellyfish valve. The motor of the RIAFBP is installed in the left ventricle, and its impeller is placed at the aortic valve position.…”
Section: Cardiac Support and Blood Pumpsmentioning
confidence: 99%
“…As a typical pulsating pump, the roller pump offers several significant advantages, including trustworthy flow rates, simple operation, and noncontact pumping, 1 which eliminates blood contamination from mechanical wear. Although the rotary pump (such as the centrifugal pump) obtained more attention from academic circles 8‐12 and it was even believed that the rotary pump would gradually render the roller pump obsolete, increasing studies showed that the centrifugal pump did not have a clear superiority over the roller pump, especially in the short term assist 2‐3,13 . Furthermore, studies have indicated that the pulsatile blood flow can bring about healthier effects such as optimization of microvascular perfusion, 14‐15 higher postperfusion cardiac output, 16 and higher rate of organ recovery 7 .…”
Section: Introductionmentioning
confidence: 99%